2017
DOI: 10.1186/s12904-016-0166-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the characteristics and subjects of pediatric palliative care case management provided by a hospital based palliative care team

Abstract: BackgroundCase management is a subject of interest within pediatric palliative care. Detailed descriptions of the content of this type of case management are lacking. We aim to describe the contents of care provided, utilization of different disciplines, and times of usage of a pediatric palliative care case management program compared for patients with malignant disease (MD) and non-malignant disease (NMD).MethodsA three-month prospective study, with questionnaires filled in by members of a pediatric palliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…The emphasis on training and valuing staff in our work is consistent with previous research which has emphasised the need to upskill staff [ 19 , 56 , 57 ]. A number of studies have highlighted the lack of recognition of the knowledge and expertise of non-qualified care staff who are most closely involved in delivering care [ 58 , 59 ] and the implications this can have for the provision of care [ 60 ]. Previous studies have also emphasised the need for person-centred management and interventions to meet the emotional support needs of care home staff [ 61 – 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis on training and valuing staff in our work is consistent with previous research which has emphasised the need to upskill staff [ 19 , 56 , 57 ]. A number of studies have highlighted the lack of recognition of the knowledge and expertise of non-qualified care staff who are most closely involved in delivering care [ 58 , 59 ] and the implications this can have for the provision of care [ 60 ]. Previous studies have also emphasised the need for person-centred management and interventions to meet the emotional support needs of care home staff [ 61 – 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The question remains as to how best to translate these findings into practice. Other studies have suggested the introduction of new roles such as a mobile specialist palliative care team in dementia to provide expert advice and to support the usual care-giving team [ 28 ], or a ‘key worker’ to co-ordinate care [ 50 ]. A number of innovative options to improve EoLC in dementia have been tested, including dementia specific hospice care [ 67 ]; specialist dementia palliative care [ 68 ]; a specialist community-based multi-disciplinary team focused on facilitating home death [ 69 ]; an ‘integrated care leader’ [ 70 ]; audit/feedback systems [ 71 ], decision support tools [ 72 , 73 ] and a multifaceted intervention in long term care [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After‐hours support, as part of an emergency management plan, may be helpful (Bradford, Irving, Smith, Pedersen, & Herbert, ), while a multidisciplinary team‐based approach that is proactive in following up issues for families, including psychosocial support and socio‐economic considerations, is also of benefit (Jagt‐van Kampen et al., ).…”
Section: Towards An Integrated Approach To Carementioning
confidence: 99%
“…The study reported here builds upon the culmination of collaborative work that entailed developing the conceptual and theoretical foundations for older person navigation [ 47 , 48 ]; creating, testing, and refining curriculum for volunteer navigators [ 49 ]; and conducting three incremental pilots to determine the feasibility and acceptability of Nav-CARE [ 50 , 51 ]. These pilots provided care to older persons living with a variety of advanced chronic illnesses, of which cancer was the most prevalent.…”
Section: Introductionmentioning
confidence: 99%